Passive force control of multimodal astronaut training robot. (24th May 2019) - Zou, Yupeng; Qin, Tao; Wang, Nuo; Li, Junqing; Xu, Ming
For the purpose of solving the problem of astronaut training in weightlessness environment, this article proposes a multimodal astronaut training robot to enable astronauts to perform running, bench press and deep squat training in the weightless environment, so as to help them mitigate the adverse effects brought by the space adaptation syndrome. Taking the modularized wire driving unit as the research object, the dynamic model of the passive force servo system was established; and the passive force control strategy was designed. The experimental results show that the system is of good stability, high steady-state accuracy, and excellent dynamic quality after correction. When the given signal frequency is 10 Hz, the system phase lag is about 9°, and the loading error is about 5%. The passive force servo control strategy can effectively reduce the surplus force. When the speed disturbance frequency of carrying unit is within 3 Hz, the elimination rate of the surplus force can reach 90%.